Pharmacology and Nutritional Intervention in the Treatment of Disease 2014
DOI: 10.5772/57372
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants as Complementary Medication in Thalassemia

Abstract: Inhibitors of iron absorption (tea, Ca) Foods (phytate and oxalate) Antioxidative compounds (vitamin C, E, NAC) Antioxidative phytochemicals (flavonoids, curcuminoids) Oxidative stress Hemosiderosis Cardiomyopathy Liver inflammation and cirrhosis Thalassemias with iron overload (From Nature Genetics Review, 2004) Endocrinopathy Ineffective erythropoiesis Hormone supplement Hb F modifiers (hydroxyurea, hydroxycarbamide, decitabin and phenylbutyrate) Hb stimulating agents (erythropoietin, folic acid) Bone marrow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 174 publications
(178 reference statements)
1
3
1
Order By: Relevance
“…In SCD subjects the protective role of HU therapy was reported to be more pronounced in patients receiving HU along with iron chelation therapy as compared to HU therapy alone . Use of antioxidants as complementary medicine in β‐thalassemia is advocated by clinicians . Our study group, however, indicated higher concentrations of ferritin in all patients (treated/untreated), suggesting an inadequate use of iron chelation therapy.…”
Section: Discussioncontrasting
confidence: 52%
“…In SCD subjects the protective role of HU therapy was reported to be more pronounced in patients receiving HU along with iron chelation therapy as compared to HU therapy alone . Use of antioxidants as complementary medicine in β‐thalassemia is advocated by clinicians . Our study group, however, indicated higher concentrations of ferritin in all patients (treated/untreated), suggesting an inadequate use of iron chelation therapy.…”
Section: Discussioncontrasting
confidence: 52%
“…We found that white meat consumption in TDT patients was less than control subjects, as far as frequency of consumption of meat per week is concerned . We found that majority of TDT patients were consuming 1-2 times per week followed by 3-4 times per week, which was comparatively higher consumption than control subjects, [16] also reported that adult thalassemia patients consumed sufficient amount of meat and vegetables which comparable with present study observed that majority of the TDT patients were consuming 5-8 cups per week as compared to control subjects. Higher consumption of tea and milk is reported to be beneficial in TDT patients because it reduces iron absorption as the TDT patients are already iron overloaded due to transfusion [17].…”
Section: Resultssupporting
confidence: 87%
“…It has been reported that supplements of the antioxidant compounds (vitamins C and E, selenium, and zinc) can prevent some of the damage in the thalassemic red blood cell membrane and ameliorate pathophysiological complications [42,74]. Recently, Yanpanitch et al [75] investigated the effects of antioxidant cocktails for the treatment of β-thalassemia/hemoglobin E (HbE), which is the most common form of β-thalassemia in Southeast Asia.…”
Section: Discussionmentioning
confidence: 99%